2022
DOI: 10.1038/s41598-022-24329-9
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from Pseudostellaria heterophylla modulate gut microbiota and alleviate syndrome of spleen deficiency in rats

Abstract: Pseudostellaria heterophylla, also called Tai-zi-shen (TZS) in Traditional Chinese Medicine (TCM), is always used clinically to treat spleen deficiency symptoms. Polysaccharides in TZS have various pharmacological activities, including anti-diabetic, immune regulation, and myocardial protection. However, the relationship between the spleen-invigorating effects of TZS or its polysaccharides and intestinal flora are not clear. This study investigated the effects of TZS decoction (PHD) and polysaccharide (PHP) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…5(a)). Alpha diversity was reflected in the Chao1 index, Shannon index and Simpson index, indicating the richness and evenness of the observed species 31,32 (Fig. 5(b-d)).…”
Section: Fqd Reversed Spleen Cell Morphology and Expression Of Apopto...mentioning
confidence: 99%
“…5(a)). Alpha diversity was reflected in the Chao1 index, Shannon index and Simpson index, indicating the richness and evenness of the observed species 31,32 (Fig. 5(b-d)).…”
Section: Fqd Reversed Spleen Cell Morphology and Expression Of Apopto...mentioning
confidence: 99%
“…Pseudostellaria heterophylla , used in Chinese Traditional Medicine, was used for palpitation, anorexia, and splenic asthenia (Hu et al, 2020; Jinlong et al, 2016; Xiao et al, 2022). P. heterophylla polysaccharides (PHP), as one of the main active ingredients of P. heterophylla , has been shown to possess a range of biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, natural polysaccharides have attracted the attention of researchers due to their safety and biological activity [9]. Studies have reported that polysaccharides extracted from TCM have few adverse effects and various biological functions on cancer [10], hyperlipidemia [11], inflammation [12], immunity [13], and antioxidation [14]. Polysaccharides from Penthorum chinense Pursh have been shown to inhibit H22 cell growth via the induction of a mitochondrial-dependent apoptosis [15].…”
Section: Introductionmentioning
confidence: 99%